John Dewey, individualismo y democracia - MOráN, Juan G. (Foro Interno, 2009)
In recent times North American pragmatist philosophy has acquired great relevance, and the figure of John Dewey stands out especially. Two of his major works on social and political philosophy —Individualism, Old and New and The Public and Its Problems— were recently published in Spanish. This paper reviews his ideas about individualism, liberalism, community, public opinion, and democracy, with an eye to their relevance for the problems and challenges of our time.
Keywords: John Dewey; Pragmatism; Individualism; Community; Democracy; United States